Pre-harvest interval profiles of selected insecticides in broccoli grown under supervised trials (Asian-Australasian Journal of Food Safety and Security, 2025)
Vegetables, including broccoli (Brassica oleracea var. botrytis), are important components of the human diet due to their high nutritional value. However, insect pests pose a major challenge to broccoli production, and pesticides are widely applied to maintain crop quality and yield. In Bangladesh, indiscriminate pesticide use often leads to residues in vegetables, posing risks to human health and the environment. This study aimed to determine the pre-harvest interval of commonly used insecticides in broccoli and compare residue levels with the maximum residue limits (MRLs) established by the European Union. Broccoli was sprayed with recommended doses of lambda-cyhalothrin, dimethoate, and chlorpyrifos plus cypermethrin at 1 mL/L, and acephate at 2 g/L, across four supervised field trials. Samples were collected at 0, 1, 3, 5, 7, 9, 11, 13, 15, and 17 days after spray (DAS), and residues were analyzed by gas chromatography using a flame thermionic detector for organophosphorus insecticides and an electron capture detector for pyrethroids. Residue levels exceeded the EU-MRL up to 11 DAS for lambda-cyhalothrin, 13 DAS for chlorpyrifos plus cypermethrin and acephate, and 15 DAS for dimethoate. The PHI was determined as 13 DAS for lambda-cyhalothrin, 15 DAS for chlorpyrifos plus cypermethrin and acephate, and 17 DAS for dimethoate. These findings provide valuable guidance for farmers on safe pesticide use and support the production of safe vegetables for consumers.Asian Australas. J. Food Saf. Secur. 2025, 9(2), 77-85